High-strength gears produced by powder metallurgical processes – KL500/93-2. Issue 6 (21st December 2019) - Klocke, Fritz; Broeckmann, Christoph; Löpenhaus, Christoph; Bezold, Alexander; Frech, Tim; Hajeck, Marko; Scholzen, Philipp; Gebhardt, Christian
Abstract : Purpose: The purpose of this study is to optimize high-strength gears produced by powder metallurgical process and to provide a material model to predict the tooth root bending fatigue strength. Powder metal (PM) technology offers great opportunities for the reduction of the carbon footprint and improvement of the cost efficiency of gear production. PM gears can achieve flank load-carrying capacities comparable to wrought steel gears if the loaded volume is fully densified. Still, the tooth root strength is of particular importance. Design/methodology/approach: The tooth root stresses can be minimized by optimizing the tooth root geometry. This usually leads to a target conflict, as fully optimized tooth root geometries cannot be manufactured by generating processes such as hobbing, generating-grinding or rolling. To use the increase in tooth root load-carrying capacity of fully optimized root geometry on PM gears, a non-generating method for surface densifying is needed. The shot-peening process is used as an alternative densification process for PM gears. The properties of both shot peened and cold-rolled PM gears are analyzed and compared. To quantify the effect of both manufacturing processes, the tooth root bending fatigue strength will be evaluated and compared to wrought gears. Findings: From the fatigue strength perspective, a material model is developed, which is able to predict local endurable stress amplitudes. The model is gained through regression varying carbon content, density and size effect on bending specimens. Originality/value: It is transferable to PM gears of the same material using a load transfer coefficient.